Lip Mesotherapy With Dexpanthenol As A Novel Approach To Prevent Isotretinoin-Associated Cheilitis - Çağrı Turan; Ümran Öner (Mattioli1885, 2023)
Introduction: Isotretinoin (ISO)-associated cheilitis is the most common side effect and the most common reason for discontinuation of ongoing therapy. So, various lip balms are also routinely recommended for all patients. Objectives: We aimed to investigate the effectiveness of local intradermal injections (mesotherapy) of dexpanthenol into the lips to prevent ISO-associated cheilitis. Methods:  This pilot study was conducted on patients over the age of 18 using ISO (about 0.5 mg/kg/day). All patients were prescribed only hamamelis virginiana distillate in ointment form as a lip balm. In the mesotherapy group (n=28), 0.1 ml of dexpanthenol was injected into each lip tubercle (4 points total) to the submucosal level. The patients in the control group (n=26) used only the ointment. "ISO cheilitis grading scale (ICGS)" was used in the evaluation of ISO-associated cheilitis. The patients were followed for 2 months. Results:  Although there was an increase in ICGS scores in the mesotherapy group compared to the baseline, no statistically significant change was observed after treatment (p=0.545). However, in the control group, there was a statistically significant increase in ICGS scores in the 1st and 2nd months compared to the baseline (p<0.001). Lip balms were needed significantly less frequently in the mesotherapy group compared to the control, both in the 1st and 2nd months (p=0.006, p=0.045; respectively). Conclusions: Lip mesotherapy with dexpanthenol will be a useful option for preventing ISO-associated cheilitis because of its easy application, cost-effectiveness, low complication risk, and high patient satisfaction.